Between Geology and Architecture. The Representation of the Archaeological Landscape of Tiermes (diségno, 2024)
In his paper The beholding eye. Ten versions of the same landscape, Donald William Meinig explores an expanded definition of what landscape is, offering an analysis of the different forms of its observation, thus demonstrating the infinite potential of the concept, capable of adapting to the gaze of those who contemplate it [Meinig 1979]. The study highlights how the landscape is endowed with powerful physical, environmental, economic, cultural, psychological and aesthetic components.Among these, cultural heritage undoubtedly stands out, a powerful element by virtue of which human beings attribute value to a given place, especially if it is in the form of a ruin, the result of protracted interaction between human activity and nature.This is particularly visible in the archaeological site of Tiermes, a man-made landscape characterised by a unique spatial condition, whose transformation by man has left us important archaeological remains, especially from the Roman era. In it, we find a convergence of morphological and topographical values that have captivated the viewer’s attention to such an extent that it has been described as ‘a gigantic architectural fossil’.This paper briefly reviews the graphic and photographic documentation generated to represent the site under study, in a vision in which geology, architecture and archaeology overlap and intermingle, and then dwells on the most recent research that –through the use of new systems of analysis and representation of architecture– offers us a new interpretation and representation of the Tiermes landscape.
Keywords: topography; ruins; archaeological landscape; iconography